THE INFLUENCE OF PROCEDURAL OPERATIONAL STANDARD IN BUILDING STUDENTS CHARACTER : A CASE STUDY OF GRADE 5 AT SDIT AL-MADINAH, MAROS - Jumardi Bachtiar (JICSA : Journal of Islamic Civilization in Southeast Asian, 2022)
This study aims to identify and analyze the application of student SOP management at SDIT Al-Madinah. The main objective of this is to identify and analyze character building for class V at SDIT Al-Madinah, to determine and analyze the effect of student SOP management on character building for fifth-grade students at SDIT Al-Madinah Maros. The method used in this research is an associative quantitative method, with data collection techniques using observation, documentation, and questionnaires. the authors use a simple regression formula with a sample of 48 respondents. Based on the results of the study, it was proven that the character of fifth-grade students at SDIT Al-Madinah Maros was significantly and positively influenced by Student SOPs. These results were obtained from testing the hypothesis using the t-value, which shows that the t-count of Student SOP is 4.234 higher than the predetermined t-table value of 2.021. Student SOP variable (X) affects student character variables, according to a significance value of 0.000 > 0.05.(Y). Based on the test of the coefficient of determination, the effect of applying Student Standard Operating Procedures on student character is 28% or R2 (R Square) of 0.280 (0.530). This shows that the independent variable (Student SOP) used can have a 28% effect on the dependent variable (student character). based on the results of a determination test of 0.280, which means a positive effect of 28% while 72% is influenced by other variables or factors that are not present in this study such as role models, environment, personality, etc. Therefore, according to the results of this study, student SOPs are classified as able to help in building student character at school.